Recruitment of Legislative Candidates with Entrepreneurial Backgrounds by Political Parties in Pekanbaru City in the 2024 Election: Rekrutmen Calon Legislatif Berlatar Pengusaha oleh Partai Politik di Kota Pekanbaru pada Pemilihan 2024 - Rika Yolanda; Ali Yusri; Muchid (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Political Parties have one important function, namely recruiting competent cadres to determine the continuity of the political system. In 2024 Indonesia will face general elections. In the run-up to the general election in Indonesia, Various phenomena occurred, one of which was the phenomenon of the increasing number of entrepreneurs getting involved or running as legislative candidates. There are arguments that say that businessmen's involvement in politics has a negative impact. This does not only happen in the center of Indonesia's capital city, but also occurs in other regions of Indonesia, one of which is Pekanbaru City. This research purpose is to identify the implementation of political party recruitment Golkar, Perindo, Nasdem and PKS Pekanbaru City for entrepreneurs who are legislative candidates for Pekanbaru City 2024. The theory used is the implementation of candidate recruitment by political parties according to Pippa Norris (Haris et al., 2016) consists of the certification stage, nomination stage and election stage. This research uses a descriptive qualitative approach. Data collection techniques used were interviews and documentation. Research location in Pekanbaru City. The results of this research show that the recruitment process carried out by the political parties Golkar, Perindo, Nasdem and PKS was carried out openly, following the systematics that apply to each party. Registration for each party reached more than 100% of the number required for the party to be registered with the Pekanbaru City General Election Commission. Internal factors owned by entrepreneurs, religious norms and self-values ​​of entrepreneurs, financial resources and motivation of legislative candidates with entrepreneurial backgrounds are internal factors for political parties recruiting entrepreneurs. Meanwhile, external factors include mass support from legislative candidates with entrepreneurial backgrounds and conditions of political change.